ENCOURAGING INTENTION IN SUSTAINABLE ENTREPRENEURSHIP THROUGH CSR SUPPORTING MECHANISMS - Nuringsih, Kartika; Maupa, Haris; Taba, Muhammad Idrus (Graduate Program of Universitas Tarumanagara, 2024)
As an effort to pursue the achievement of sustainable development goals (SDGs) in higher education, this study identifies the potential for growing student interest in sustainable entrepreneurship. The basic idea in this study is to involve corporate social sustainability (CSR) as a support for forming interest in prospective and new entrepreneurs in this model. For this reason, the goal of this research is to identify the relationship between perceived CSR support and students' intentions for sustainable entrepreneurship. Entrepreneurial students were selected as a sample (n=90) using a convience sampling method. The validity and reliability testing indicate that the six indicators of sustainable entrepreneurial intention are valid and reliable. The same results occurred for ten indicators of perceived CSR support. Results show a significant influence of perceived CSR support on sustainable entrepreneurial intention. The path coefficient produces a t-statistical value (16.735) with a p-value (0.000) so that the hypothesis is accepted at the 5 percent significance level. The regression results produce an R-square of 0.665 with an adjusted R-square of 0.661, thus depicting a relatively large contribution in forming sustainable entrepreneurial intention. The contribution of other factors was identified as 43.90 percent in forming this intention. These results are in accordance with the theory of planned behavior, theory of triple bottom line, and theory of pyramid CRS. The supporting realizes a balance between achieving economic growth, social welfare, and environmental sustainability. The formation of good perceptions regarding CSR support indicates that this mechanism is one of the entrepreneurial ecosystems that can be relied upon to support an atmosphere of sustainability in entrepreneurial learning and practice. As a suggestion, it is necessary to increase stakeholder involvement in education sector so that it will be in line with the SDGs agenda in 2030.